Powerful words more than 200 years of extraordinary writing by African Americans - Hudson, Wade 1946- (Scholastic Nonfiction, 2004)
A collection of speeches and writings by African Americans, with commentary about the time period in which each person lived, information about the speaker/writer, and public response to the words.